The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1029/2009jd013310
|View full text |Cite
|
Sign up to set email alerts
|

Columnar aerosol optical properties in the Po Valley, Italy, from MFRSR data

Abstract: [1] The Po Valley is one of the most polluted areas in Europe. In order to provide a further contribution to the characterization of aerosol optical properties in this area, a more than 2 yr set of Multi Filter Rotating Shadow-band Radiometer (MFRSR) measurements performed from September 2006 to May 2009 at Bologna, in northern Italy, were analyzed, paying particular attention to calibration, cloud screening, and uncertainty assessment of the measurements. The results show that daily mean aerosol optical depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…7 for Avignon (<ÅE> = 1.43) and Ispra (<ÅE> = 1.51) over Western Europe were influenced by industrial, urban, and traffic pollutants, such as ammonium salts of sulphate and nitrate (González et al, 2000;Benkovitz et al, 1996;Kambezidis and Kaskaoutis, 2008;Mazzola et al, 2010). The seasonal variation ofÅE is small as the major source during the year is industrial pollutant.…”
Section: Western Europementioning
confidence: 99%
“…7 for Avignon (<ÅE> = 1.43) and Ispra (<ÅE> = 1.51) over Western Europe were influenced by industrial, urban, and traffic pollutants, such as ammonium salts of sulphate and nitrate (González et al, 2000;Benkovitz et al, 1996;Kambezidis and Kaskaoutis, 2008;Mazzola et al, 2010). The seasonal variation ofÅE is small as the major source during the year is industrial pollutant.…”
Section: Western Europementioning
confidence: 99%
“…In other sites in the Western Mediterranean like Avignon, Ispra, Rome, Toulon and Lecce, AOD(440 nm) and α(440-870 nm) are larger than those obtained in Granada and in other more polluted sites in the Iberian Peninsula such as Valencia and Barcelona. This is because these cities (Avignon, Ispra, Rome, Toulon and Lecce) are urban areas with high local anthropogenic emissions and quite affected by highly polluted air-masses from Europe (e.g., Pace et al, 2006;Santese et al, 2008;Mazzola et al, 2010). In addition, they are also affected by Saharan dust intrusions (e.g., Perrone et al, 2005;Santese et al, 2008;Meloni et al, 2007;Pavese et al, 2009).…”
Section: Inter-comparison With Surrounding Aeronet Stationsmentioning
confidence: 99%
“…Although the study of Kaufman et al (2000) revealed that Terra and Aqua measurements can represent the annual average value within 2 % error, still, the incomplete temporal samplings of aerosol optical properties may be incapable of faithfully reproducing the diurnal variations of aerosol optical properties, especially for SSA and g. Therefore, the aerosol optical properties are usually assumed to be constants (Sena et al, 2013;Myhre, 2009) or with negligible variability through the day of interest (Remer and Kaufman, 2006). So far, significant diurnal changes of AOD have been frequently observed in many polluted regions around the world (Zhang et al, 2012;Mazzola et al, 2010;Smirnov et al, 2002), but diurnal changes of SSA and g for ambient aerosol are rarely investigated.…”
Section: Introductionmentioning
confidence: 99%